The longitudinal outcomes of applying non-selective beta-blockers in portal hypertension: real-world multicenter study - Kang, Seong Hee; Lee, Minjong; Kim, Moon Young; Lee, Jun Hyeok; Jun, Baek Gyu; Kim, Tae Suk; Choi, Dae Hee; Suk, Ki Tae; Kim, Young Don; Cheon, Gab Jin; Kim, Dong Joon; Baik, Soon Koo (Hepatology international, 2021)
Background/Aim We investigated the effect of non-selective β-blockers (NSBB) in real-world situations and whether low-dose NSBB is beneficial compared to maximally tolerated doses. Methods We performed a retrospective study of 740 patients with cirrhosis requiring prophylactic treatment of esophageal varices: 473 primary prophylaxis (PP: NSBB = 349, non-NSBB = 124) and 267 secondary prophylaxis (SP: NSBB = 200, non-NSBB = 67). The NSBB group was divided into low-dose (≤ 80 mg/day) and high-dose (> 80 mg/day). Results In the PP group, NSBB treatment reduced mortality and showed the most pronounced effect in patients with moderate/severe ascites (hazard ratio [HR], 0.46; p < 0.01), HVPG ≥ 16 mmHg (HR, 0.53; p = 0.04), or CTP class B/C (HR, 0.46; p < 0.01) but not in those with no/mild ascites, HVPG < 16 mmHg, or CTP class A. Low-dose NSBB group showed a significant reduction in mortality compared with non-NSBB (moderate/severe ascites: HR, 0.61; p = 0.02 and CTP class B/C: HR, 0.41; p < 0.01) and the effect size was stronger than the high-dose NSBB. NSBB was associated with a reduced risk of infection (HR, 0.36; p = 0.01). In the SP group, NSBB prolonged survival in patients with moderate/severe ascites (HR, 0.56; p = 0.02), HVPG ≥ 16 mmHg (HR, 0.42; p < 0.01), or CTP class B/C (HR, 0.52; p < 0.01). Low-dose NSBB was more beneficial with 56% risk reduction ( p < 0.01) of mortality compared with 33% risk reduction in the high-dose NSBB ( p = 0.05). Conclusion NSBB therapy was associated with longer survival in PP and SP groups who had an advanced stage of cirrhosis. Moreover, low-dose NSBB exhibited a better benefit than a standard-titrated high-dose NSBB with better tolerability.